Managing novel orally administered anticoagulants in patients undergoing urogynaecological surgery. Issue 4 (April 2016) - McCarthy, Claire; O'Sullivan, Orfhlaith; O'Reilly, Barry
Abstract The use of novel orally administered anticoagulant agents (NOACs) provides new challenges to clinicians in the perioperative care of patients undergoing urogynaecological surgery. We aimed to assess evidence for managing patients taking NOACs before and after urogynaecological surgery. We conducted a literature search in CINAHL, MEDLINE, CENTRAL, Cochrane Library and PubMed for original research articles in the English language on this topic. However, despite initially identifying 556 articles, no articles pertained to the use of NOACs in urogynaecological surgery. We subsequently reviewed national and international guidance on managing patients prescribed NOACs and created a concise guideline to aid urogynaecologists in the perioperative care of these patients. Consensus is needed on perioperative optimisation of anticoagulation in urogynaecological patients using NOACs.